2013
DOI: 10.1590/s0100-29452013000300019
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade genética em coleções amazônicas de germoplasma de cupuaçuzeiro [Theobroma grandiflorum (Willd. ex Spreng.) Schum.]

Abstract: ALEXANDRE MAGNO SEBBENN 6RESUMO-Este trabalho teve por finalidade avaliar a diversidade genética e o parentesco de 24 acessos de Theobroma grandiflorum, introduzidos de três unidades da Embrapa, objetivando sua utilização como genitores no programa de hibridação da espécie. Os marcadores genéticos utilizados foram lócus heterólogos de microssatélites desenvolvidos para cacaueiro. Foram encontrados 45 alelos na população estudada. O número médio efetivo de alelos por lócus (2,33) foi menor do que o número médio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
1
16
1
3
Order By: Relevance
“…However, Lanaud et al (1999) and Alves et al (2013) reported a lower mean number of alleles per locus for T. cacao and T. grandiflorum, respectively, than that found for T. speciosum in the current study, i.e., 4.4 alleles per locus for T. cacao and 3.21 alleles per locus for T. grandiflorum.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…However, Lanaud et al (1999) and Alves et al (2013) reported a lower mean number of alleles per locus for T. cacao and T. grandiflorum, respectively, than that found for T. speciosum in the current study, i.e., 4.4 alleles per locus for T. cacao and 3.21 alleles per locus for T. grandiflorum.…”
Section: Discussioncontrasting
confidence: 93%
“…However, native Theobroma species have been subjected to strong anthropogenic genetic erosion (Alves et al, 2013), which has isolated populations into small fragments, decreased the number of individuals and the population density, and affected genetic processes such as genetic drift, gene flow, selection, and mating systems (Young and Boyle, 2000). According to Costa et al (2011), knowing the genetic variation of native species enables the development of strategies that allow the domestication and incorporation of these species in regional productive systems, as well as minimizing the environmental impact and establishing effective conservation plans.…”
Section: Introductionmentioning
confidence: 99%
“…O gênero Theobroma L., pertencente à família Malvaceae (ALVERSON et al, 1999), tem apresentado grande importância devido à relevância econômica do cacaueiro (Theobroma cacao L.) e do cupuaçuzeiro Theobroma grandiflorum (Willd. ex Spreng.)…”
Section: Introductionunclassified
“…This disease is caused by the Crinipellis (Moniliophthora) perniciosa fungus and is responsible for great yield losses observed in recent years (Alves et al, 2010). Studies on the genetic diversity of cupuaçu were carried out by Alves et al (2013), Araújo et al (2002) and Maia et al (2011a, b).…”
Section: Introductionmentioning
confidence: 99%